2015
DOI: 10.5539/jsd.v8n3p10
|View full text |Cite
|
Sign up to set email alerts
|

Actor Positions on Primary and Secondary International Forest-related Issues Relevant in Indonesia

Abstract: Over the last 20 years a considerable number of international forest-related policies has evolved, collectively referred to as the international forest regime complex. The objectives of this study are to identify the most relevant international forest-related issues discussed in Indonesia as well as the most active actors and their positions on these issues. The empirical methods used include content analysis of Indonesian newspapers, national expert journals, expert mailing lists, and international organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…As this exact type of analysis on the substantive inclusion of gender and gender mainstreaming principles in REDD+ documents has not been done previously, the methodology for analysis is based on content analysis, which has been used in other studies of REDD+ policies (Sadath & Krott, 2013;Wibowo & Giessen, 2015), and rooted firmly in the three theoretical frameworks outlined in section three.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As this exact type of analysis on the substantive inclusion of gender and gender mainstreaming principles in REDD+ documents has not been done previously, the methodology for analysis is based on content analysis, which has been used in other studies of REDD+ policies (Sadath & Krott, 2013;Wibowo & Giessen, 2015), and rooted firmly in the three theoretical frameworks outlined in section three.…”
Section: Methodsmentioning
confidence: 99%
“…Because these projects are supported and funded by a variety of different agencies, there is no one comprehensive list of REDD+ projects in the country, which necessitated an Internet search in order to identify both the projects and the documentation associated with the projects. A similar Internet keyword search methodology has been used with other forestry sector and REDD+ related research (Wibowo & Giessen, 2015). The search for documentation of REDD+ projects in Indonesia was conducted in May 2013 using the search engine Google.…”
Section: Document Selectionmentioning
confidence: 99%
“…Krott et al [62] stated that the stronger power is exercised through day-to-day implementations at the local level in the forest. According to Peters (2010) as cited by Wibowo and Giessen [16], only a single actor has a dominant role in a particular sector, and intersection of responsibilities among state bureaucracies will create conflict of interests and unproductive contestation [105][106][107]. For example, the ADB [95] reported that the conflict between the forest ministry and department created over the dissatisfaction with the department during the final project design for the "Sundarbans Biodiversity Conservation Project-1999."…”
Section: Power and Conflict Of Interest Among State Bureaucraciesmentioning
confidence: 99%
“…Here, the observable facts are linked to obvious action, threat of action, and sources of action, which are considered to be the possible sources of power. These elements might be attributed to one actor, or distributed among a number of actors, which is echoed in the policy tasks assigned to specific actors by policies of a given country [16]. Below (Table 1) is a brief description of each element.…”
Section: Bureaucratic Politics and Actor-centered Powermentioning
confidence: 99%
See 1 more Smart Citation